The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/20406223211063020
|View full text |Cite
|
Sign up to set email alerts
|

The interaction and pathogenesis between cognitive impairment and common cardiovascular diseases in the elderly

Abstract: Both cognitive impairment and cardiovascular diseases have a high incidence in the elderly population, increasing the burden of care and reducing the quality of life. Studies have suggested that cognitive impairment interacts with cardiovascular diseases such as coronary heart disease, abnormal blood pressure, heart failure, and arrhythmia. On one hand, cognitive impairment in the elderly influences the progression and self-management of cardiovascular diseases and increases the risk of cardiovascular-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 103 publications
1
15
0
3
Order By: Relevance
“… 48 Moreover, the endothelial dysfunction that characterizes CMDs can disrupt the integrity of the blood–brain barrier, leading to impaired amyloid-β clearance. 49 At the intersection of many of these mechanisms is inflammation, which plays a well-established role in the pathogenesis of CMDs 50 and may accelerate the progression of both neurodegenerative and vascular brain pathologies. 51 , 52 Elucidating the mechanisms by which cardiometabolic multimorbidity impacts dementia will require future studies integrating longitudinal measures of cognitive function with neuropathological, genetic, and biomarker data.…”
Section: Discussionmentioning
confidence: 99%
“… 48 Moreover, the endothelial dysfunction that characterizes CMDs can disrupt the integrity of the blood–brain barrier, leading to impaired amyloid-β clearance. 49 At the intersection of many of these mechanisms is inflammation, which plays a well-established role in the pathogenesis of CMDs 50 and may accelerate the progression of both neurodegenerative and vascular brain pathologies. 51 , 52 Elucidating the mechanisms by which cardiometabolic multimorbidity impacts dementia will require future studies integrating longitudinal measures of cognitive function with neuropathological, genetic, and biomarker data.…”
Section: Discussionmentioning
confidence: 99%
“…After coronary artery bypass graft (CABG) surgery, arrhythmia is another common symptom, occurring in approximately 20 to 40% of patients [ 27 ]. Atrial fibrillation has been identified as a significant risk factor of cognitive impairment [ 28 , 29 ]. Moreover, CABG surgery is also related to cognitive impairments, with around 50% of patients with cognitive impairment after 1 to 5 years post-surgery [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multimorbidity is prevalent in the elderly population, particularly cardiovascular diseases co-occurring with cognitive deficits [ 30 , 31 ]. However, the pathogenesis of these comorbidities remains unclear, although it is possible that cardiovascular disease and cognition may share several biological pathways [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multimorbidity is prevalent in the elderly population, particularly cardiovascular diseases co-occurring with cognitive deficits [ 30 , 31 ]. However, the pathogenesis of these comorbidities remains unclear, although it is possible that cardiovascular disease and cognition may share several biological pathways [ 31 ]. Cardiovascular diseases may induce vascular pathogenesis, structural changes in the brain, inflammation, immunomodulation, and endocrine and metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%